1979
DOI: 10.3133/ofr791668
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite-clay mineral zonation of volcaniclastic sediments within the McDermitt caldera complex of Nevada and Oregon

Abstract: Volcaniclastic sediments deposited in the moat of the collapsed McDermitt caldera complex have been altered chiefly to zeolites and potassium feldspar* The original rhyolitic and peralkaline ash-flow tuffs are included in conglomerates at the caldera rims and grade into a lacustrine series near the center of the collapse. The tuffs show a lateral zeolitic alteration from almost fresh glass to clinoptilolite, clinoptilolite-mordenite, and erionite; to analcime-potassium feldspar; and finally to potassium feldsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 2 publications
2
19
0
Order By: Relevance
“…However, Hofstra et al [50] and Benson et al [14] found that lithium concentrations in melt inclusions in quartz phenocrysts of both peralkaline The proportion of sediments deposited pre-and post-resurgence is uncertain because of the poor exposure and difficulty in evaluating what has or has not been resurgently domed. Most previous interpretations are that the sediments were deposited post-resurgence in a moat between the caldera wall and the resurgent uplift [5,6,44]. However, the inward dip of sediments near the caldera wall and gentle dips off the uplift suggest some sediments were deposited before resurgence.…”
Section: Intra-caldera Tuffaceous Sedimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, Hofstra et al [50] and Benson et al [14] found that lithium concentrations in melt inclusions in quartz phenocrysts of both peralkaline The proportion of sediments deposited pre-and post-resurgence is uncertain because of the poor exposure and difficulty in evaluating what has or has not been resurgently domed. Most previous interpretations are that the sediments were deposited post-resurgence in a moat between the caldera wall and the resurgent uplift [5,6,44]. However, the inward dip of sediments near the caldera wall and gentle dips off the uplift suggest some sediments were deposited before resurgence.…”
Section: Intra-caldera Tuffaceous Sedimentsmentioning
confidence: 99%
“…Chemical information reported below was obtained from Lithium Nevada drill-hole sample analyses for which contents of Li and other elements were obtained using four-acid "near total" digestion followed by ICP-MS and ICP-AES analyses by ALS Chemex. Almost all of the chemical data were from the Thacker Pass area, but some Li data came from an earlier report by the US Geological Survey [5] and from Chevron Minerals. As of June 2011, Lithium Nevada had drilled and assayed 202 core holes in the Thacker Pass area with a total depth of 19,259 m, producing a total of 11,157 samples [16].…”
Section: Chemical Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…They contain 0.25 to 0.65 ppm Hg as far away as several kilometers from the deposits. Around the lake-bed deposits-sediments have been altered to a variety of zeolite and clay facies, which Glanzman and Rytuba (1979) attributed to hydrothermal alteration, while Wallace and Roper (1981) believed the minerals are of diagenetic origin. Pyrite accompanies the cinnabar , and uranium and lithium minerals are also present locally (see below).…”
Section: Mercury Depositsmentioning
confidence: 99%